Controlling Through-Slice Chemical-Shift Artifacts for Improved Non-Fat-Suppressed Musculoskeletal Turbo-Spin-Echo Magnetic Resonance Imaging at 7 T. Issue 9 (September 2021) - von Deuster, Constantin; Sommer, Stefan; Germann, Christoph; Hinterholzer, Natalie; Heidemann, Robin M.; Sutter, Reto; Nanz, Daniel
Abstract : Objectives: Through-slice chemical shift artifacts in state-of-the-art turbo-spin-echo (TSE) images can be significantly more severe at 7 T than at lower field strengths. In musculoskeletal applications, these artifacts appear similar to bone fractures or neoplastic bone marrow disease. The objective of this work was to explore and reduce through-slice chemical shift artifacts in 2-dimensional (2D) TSE imaging at 7 T. Materials and Methods: This prospective study was approved by the local ethics board. The bandwidths of the excitation and refocusing radiofrequency (RF) pulses of a prototype 2D TSE sequence were individually modified and their effect on the slice profiles and relative slice locations of water and fat spins was assessed in an oil-water phantom. Based on these results, it was hypothesized that the combination of m atched and i ncreased excitation and refocusing RF pulse b andwidths ("MIB") of 1500 Hz would enable 2D TSE imaging with significantly reduced chemical shift artifacts compared with a state-of-the-art sequence with u nmatched and m oderate RF pulse b andwidths ("UMB") of 1095 and 682 Hz. A series of T1-weighted sagittal knee examinations in 10 healthy human subjects were acquired using the MIB and UMB sequences and independently evaluated by 2 radiologists. They measured the width of chemical shift artifacts at 2 standardized locations and graded the perceived negative effect of chemical shift artifacts on image quality in the bones and in the whole gastrocnemius muscle on a 5-point scale. Similar knee, wrist, and foot images were acquired in a single subject. Signal-to-noise ratios in the femoral bone marrow were computed between the UMB and MIB sequences. Results: Phantom measurements confirmed the expected spatial separation of simultaneously affected water and fat slices between 40% and 200% of the prescribed slice thickness for RF pulse bandwidths between 2500 and 500 Hz. Through-slice chemical shift artifacts at the bone-cartilage interface were significantly smaller with MIB than with UMB (location 1: 0.35 ± 0.20 mm vs 1.27 ± 0.27 mm, P < 0.001; location 2: 0.25 ± 0.13 mm vs 1.48 ± 0.46 mm, P < 0.001; intraclass correlation coefficient = 0.98). The negative effect of chemical shift artifacts on image quality was significantly smaller with MIB than with UMB (bone: 2 ± 0 vs 4 ± 1, P < 0.004 [both readers]; muscle: 3 ± 0 vs 2 ± 0, P < 0.004 [both readers]; κ = 0.69). The signal-to-noise ratio of the UMB and MIB sequences was comparable, with a ratio of 99 ± 7%. Images acquired using the UMB sequence displayed numerous artifactual hyperintensities and diffuse, as well as locally severe, fat signal loss in all examined regions, whereas the MIB sequence consistently yielded high image quality with bright T1-weighted fat signal and excellent depiction of fine tissue structures. Conclusions: On 7 T systems, the selection of high and matched RF bandwidths for excitation and refocusing pulses for 2D TSE imaging without fat suppression showed consistently better image quality than state-of-the-art sequences with unmatched lower RF pulse bandwidths.